2019
DOI: 10.1038/s41598-019-46516-x
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain inhibitor JQ1 reversibly blocks IFN-γ production

Abstract: As a class, ‘BET’ inhibitors disrupt binding of bromodomain and extra-terminal motif (BET) proteins, BRD2, BRD3, BRD4 and BRDT, to acetylated histones preventing recruitment of RNA polymerase 2 to enhancers and promoters, especially super-enhancers, to inhibit gene transcription. As such, BET inhibitors may be useful therapeutics for treatment of cancer and inflammatory disease. For example, the small molecule BET inhibitor, JQ1, selectively represses MYC , an important oncogene regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Overall, these data indicate that DM2 + CVD monocytes are hyperactivated by the pro-M1 stimulant IFNγ, leading to an enhanced expression of chemokines and genes within the NF-κB pathway. Previous reports have indicated that IFNγ signalling is sensitive to BET inhibition [25,45,48,49]. Ex vivo treatment with apabetalone suppressed the transcription of genes that responded differentially to IFNγ, namely CCL8, TNF, RELA, MYD88, CCL7 and IFITM1 (Fig.…”
Section: Apabetalone Counters Dm2 + Cvd Monocyte Hyper-responsivenessmentioning
confidence: 73%
“…Overall, these data indicate that DM2 + CVD monocytes are hyperactivated by the pro-M1 stimulant IFNγ, leading to an enhanced expression of chemokines and genes within the NF-κB pathway. Previous reports have indicated that IFNγ signalling is sensitive to BET inhibition [25,45,48,49]. Ex vivo treatment with apabetalone suppressed the transcription of genes that responded differentially to IFNγ, namely CCL8, TNF, RELA, MYD88, CCL7 and IFITM1 (Fig.…”
Section: Apabetalone Counters Dm2 + Cvd Monocyte Hyper-responsivenessmentioning
confidence: 73%
“…Thus, in cell types where AR regulation of ACE2 and TMPRSS2 does not exist, the broader transcriptional repression by BET inhibitors may block expression of these key host factors, and agents targeting BET proteins may have a different therapeutic efficacy in COVID-19 than direct AR inhibitors. BET inhibitors can also affect innate and adaptive immune responses, through processes such as repression of IFNG (IFN gamma) ( 32 ), which could potentially attenuate the cytokine storm associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IFN-γ seRNA maintains the interaction of NF-κB with IFN-γ locus, which boosts innate and adaptive immune responses against cancer progression [119]. Preclinical data showed that BET inhibitor JQ1 prominently abrogates BRD4-associated IFN-γ seRNA and IFN-γ production via suppressing RNA Pol II binding to the IFN-γ locus, which results in dysfunction of CD4+ T and NK cells, following by the weak immune response [91].…”
Section: Serna Participates In Immune Responsementioning
confidence: 99%